THE FREQUENCY OF LISTENING TO ENGLISH SONGSAND LISTENING ACHIEVEMENT - Ria Yuli Angliawati, - (2011)
This study investigates a correlation between the frequency of listening to English songs and listening achievement, involving 30 students of the third year of English Department of Indonesia University of Education and using Pearson Product Moment Correlation and Coefficient. Data were obtained from the questionnaire distributed to the students and the results of a listening test administered by the department. Data from the questionnaire were then analyzed to investigate the students' frequency of listening to English songs and other supporting information needed in analyzing its correlation with listening achievement. The result shows the correlation coefficient of 0.759 is significant at the level of 0.05. This indicates there is a high relationship between the frequency of listening to English songs and listening achievement amongst the participants. In other words, by having a high frequency of listening to English songs students can probably have a good listening achievement. It is thus recommended that further study be conducted concerning the topic.